Free amino acids in plasma and brain after chronic manganese intake in rats - Bonilla, Ernesto; Prasad, Annavajhala L.N.; Dávila, José; Arrieta, Arelis; Villalobos, Rudy (Investigación Clínica, 2013)
We studied the levels of several free amino acids in blood plasma, striatum and frontal cortex of adult rats treated during eight months with manganese chloride added to the drinking water. No significant difference could be demonstrated in any of the amino acids analyzed.